DETERMINAN KINERJA PERUSAHAAN ASURANSI JIWA DI INDONESIA - Nurlaili, Alifatun; Hariyati, Hariyati (Jurnal Akuntansi AKUNESA, 2020)
Insurance is a risk transfer institution. The development of insurance companies is reflected by company?s performance. Every company has to maintain its performance always good and healthy. This study aims to examine the effect of liquidity, company size, reinsurance dependency, and leverage on the performance of life insurance companies in Indonesia in 2013-2017. The research sample consisted of 21 companies using panel data regression analysis techniques to determine the best estimation model between CEM, FEM and REM. The results showed the best estimation model was REM and firm size had a positive effect on company performance, liquidity andleverage has a negative effect on company performance, while reinsurance dependence does not affect company performance.